2020
DOI: 10.1210/jendso/bvaa040
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Partner Perspectives on Health-Related Quality of Life in Adrenocortical Carcinoma

Abstract: Little is known about the impact of adrenocortical carcinoma (ACC) on health-related quality of life (HRQoL), and no disease-specific questionnaire exists. This qualitative study aimed to identify relevant domains of HRQoL for patients with ACC. In 2 focus group interviews, we discussed concerns regarding living with ACC and its treatments. The first group consisted of 6 patients on mitotane therapy and their partners or relatives, the second group of 4 patients after surgery alone and their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Cognitive impairment in adults usually presents with confusion, decreased concentration and memory impairment. Psychological effects have been reported with mood swings, panic attacks, burn-out and even clinical depression [ 37 ]. These neurotoxic effects appear to be partly or completely reversible after cessation of mitotane, same as in children [ 15 , 38 , 39 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Cognitive impairment in adults usually presents with confusion, decreased concentration and memory impairment. Psychological effects have been reported with mood swings, panic attacks, burn-out and even clinical depression [ 37 ]. These neurotoxic effects appear to be partly or completely reversible after cessation of mitotane, same as in children [ 15 , 38 , 39 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the first phase, a comprehensive list was composed of potential HRQoL issues that patients with ACC might face. This was done using a systematic literature search and focus group interviews, of which the methods and results can be found in more detail in previous publications [6,8]. In short, we found 6 studies that assessed HRQoL in patients with ACC and listed the reported issues.…”
Section: Phase I-issue Identificationmentioning
confidence: 99%
“…Patients with ACC experience many combinations of issues which can impair HRQoL [8]. Examples of these issues are mitotane side-effects, hormone excess, problems with sexuality, and concerns about scan results.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that higher replacement dose of glucocorticoid was required to treat AI related to ACC (AI/ACC) and to prevent adrenal crisis, compared with other causes of AI 14–16 . Whilst qualitative data on living with ACC is available, a scoping review revealed no qualitative patient experience evidence for living with AI related to ACC 17 . This systematic review aimed to understand patient lived experience and wellbeing in AI secondary to ACC using evidence from a variety of study designs and thereby extract evidence related to the impact and management of this condition on patient wellbeing to inform a holistic approach to person‐centred care.…”
Section: Introductionmentioning
confidence: 99%